A Imprensa Francófona no Brasil: circulação transnacional e cultura midiática nos séculos XIX e XX - Guimarães, Valéria Dos Santos (Universidade Estadual Paulista Julio de Mesquita Filho, 2019)
ABSTRACT Francophilia has been present in Brazil since the late eighteenth century, and French-language periodicals imported from Paris as well as national newspapers and magazines published by emigrants in the following centuries were responsible for its dissemination. This article is devoted to some questions about the production, circulation and distribution of French and French-Brazilian newspapers and magazines in the cities of Rio de Janeiro and São Paulo in the 19th and 20th centuries. The hypothesis is that this printed press performed the Francophone diffusion and was between the pioneers of insertion of Brazil in the logic of transnational media that appears with rise of modernity. To this end, in addition to get lists of French printed press imported and local published titles in two capitals, achieved in old catalogs of book sellers and public collections, as well as the distribution places which made them accessible to readers, were consulted French and Brazilian statistical and postal reports to search quantitative data of subsidies the analysis. Between results were found titles French predominance (result the French power culture in this period, particularly in Latin America) and the discovery of commercial deals favorable to French printed press, which bring a new element to explain its great influx to Brazil, indicating a new methodological perspective for the studies of the foreign press circulation history.

RESUMO A francofilia esteve presente no Brasil desde fins do século XVIII, presença também materializada na circulação de periódicos tanto importados de Paris, como publicados por emigrados nos séculos seguintes. O objetivo deste artigo é discorrer sobre aspectos da produção, circulação e distribuição desses periódicos no Rio de Janeiro e em São Paulo. A hipótese é que eles tanto difundiam a cultura francófona, como foram pioneiros na inserção do Brasil na lógica da cultura midiática transnacional da modernidade. Além do levantamento de títulos importados e impressos no país em catálogos antigos de livreiros e de acervos públicos e dos locais de distribuição ao leitor, foram consultados relatórios estatísticos e dos correios franceses e brasileiros em busca de dados quantitativos. Entre os resultados está a constatação do predomínio de títulos em francês em relação aos demais idiomas estrangeiros (dada à força global da cultura francesa no período, particularmente na América Latina) e a descoberta de acordos comerciais favoráveis à entrada de impressos provenientes da França, dado inédito revelado pela análise dos relatórios oficiais, o que traz um novo elemento para explicar o seu grande afluxo para o Brasil, apontando uma nova perspectiva metodológica para os estudos da circulação da história da imprensa estrangeira.
Francophone printed press in Brazil: transnational circulation and media culture in 19th and 20th centuries
Keywords: Francophone press; transnational; cultural mediators; Brazil; History of Reading; Imprensa francófona; transnacional; mediadores culturais; Brasil; História da Leitura